(untitled) (Bangladesh Journal of Medical Physics, 2013)
Some pancake and spherical type ionization chambers of various size have been designed and fabricated for absolute air kerma measurement in 60Co and 137Cs ?-ray fields at the Primary Standard Dosimetry Laboratory (PSDL), National Institute of Advanced Industrial Science & Technology (AIST), Tsukuba, Japan. Values of recombination parameters A and m2g of these ionization chambers are obtained using a method proposed by De Almeida and Niatel and adopted by Boutillon. For absolute air kerma measurement, it is important to obtain accurate signal currents by correcting it for ion losses using the values of A and m2g of each of the ionization chambers. It has been observed from the measurements that the recombination parameters for pancake ionization chamber are smaller than spherical ionization chambers and for spherical type ionization chamber recombination parameter values depend on the dimensions of the electrodes and also the size of the chambers. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14694 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 101-106